(3Gdeaghe (B-(3GdGSGSjGJ (B-(3GdeHGOF(B-(3GdCgejIs - (3fYje GHQGgje(B, (3GdXGgQs ((3GQHO(B:s (3YGde GdcJH GdMOjK(B,s, 2009)
1)(3eGgjI GdfXe GdGOGQjI (B: (3aj GdeaGgje GdGOGQjI , eaGgje GdfXe , Gdgjcd GdJfXjej aj GdGOGQI GdeYGUQI , GdYfGUQ GdHjFjI GdeDKQI aj GdefXeI (B2) (3GdGJLGgGJ GdMOjKI ddfXe GdGOGQjI (B3)(3fXe CJeJI GdecGJH (B4) (3fXe OYe GdbQGQ (B5) (3GdPcGA GdUfGYj h GdfXe GdNHjQI (B6) (3fXe GdeYdheGJ GdGOGQjI (B: (3EOGQI GdeYdheGJ , JWhjQ h HfGA fXe GdeYdheGJ , ef CHQR GdNUGFU GdSjGSjI ddOhd GdZQHjI h GdeJbOeI (B.s
(3eQGLY U(B.346(3; GTcGd (B: (3dcd Tcd U;LOGhd (B: (3dcd LOhd U(B.s
Keywords: (3GdEOGQIs; (3JbfjGJ GdEOGQIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s